A Study of Sport Tourists Participate Motivation, Travel Experience, Perceived Value, and Behavioral Intention in Marine Sport Tourism (Global Journal of Management and Business Research, 2017)
The purpose of this study was to analyzed marine sport tourism participate motivation, travel experience, perceived value, behavioral intention of tourist. A total of 1219 valid questionnaires were conducted in Penghu, Taiwan, and non-randomized survey was conducted for tourists who participated in marine recreational activities. After the descriptive statistic and analysis of PLS, the results show that marine sport tourism attractions will directly affect the travel experience and perceived value of tourist, and the above two variables will also affect the behavioral intention of the tourist for the destination. Based on the above findings, this study not only advises on marine recreational operations and managers, but also provides research for future researchers.
Keywords: participate motivation; travel experience; perceived value; behavioral intention